Analysis of the Health Level of Regional Development Banks Before and During the Covid-19 Pandemic Using the RGEC Approach in the Sumatra Region - Batubara, Mhd. Zulfadli; Sadalia, Isfenti; Wibowo, Rulianda Purnomo (East Asian Journal of Multidisciplinary Research, 2024)
This study aims to analyze the health level of regional banks before and during the pandemic period 2017-2022 in the Sumatra region. Sampling in this study were all regional development banks in the Sumatra region, totaling 8 banks. This research analysis uses the RGEC method (Risk Profile, Good Corporate Governance, Earnings and Capitals). The results of this study indicate that the health level of regional development banks for the 2017-2022 period is 90.38%, overall the condition of the Bank is in a very healthy condition while for bank health in the pre-covid period (2017-2019) of 89.30% and during the pandemic period (2020-2022) of 91.52%, from the results of this study it is stated that there is a growth in the level of bank health before and during the pandemic of 2.22%. This study also analyzed the T test to find differences before and during the pandemic using variables (NPL, LDR, ROA, NIM and CAR) for the LDR, NIM and CAR variables showed significantly different while for the GCG variable using the Wilcoxon test it was found to be significantly different before and during the pandemic.